First Total Synthesis of (β-5)-(β-O-4) Dihydroxytrimer and Dihydrotrimer of Coniferyl Alcohol (G): Advanced Lignin Model Compounds - Flourat, Amandine L.; Peru, Aurélien A. M.; Haudrechy, Arnaud; Renault, Jean-Hugues; Allais, Florent (Frontiers in Chemistry, 2019)
To investigate lignin degradation, scientists commonly use model compounds. Unfortunately, these models are most of the time simple β-O-4 dimers and do not sufficiently mimic the wide complexity of lignin structure (i.e., aliphatic side chains and robust C-C bonds). Herein, we present a methodology to access advanced lignin models through the first synthesis of two trimers of monolignol G - possessing side-chains and both robust β-5 bond and labile β-O-4 bond - via a chemo-enzymatic pathway. Key steps were (1) the C-C coupling via laccase-mediated oxidation, (2) the C-O coupling via a simple SN2 between a phenolate and a bromoketoester and (3) modified Upjohn dihydroxylation or palladium-catalyzed hydrogenation. (β-5)-(β-O-4) trimer and dihydrotrimer of coniferyl alcohol (G) were obtained in good global yield, 9% and 20%, respectively, over 9 steps starting from ferulic acid.